Prevention and treatment of non-complicated infections of the lower urinary tract in pregnant women - N.A. Nashivochnikova; V.N. Krupin; V.E. Leanovich (LCC «Medicine-Inform», 2021)
N.A. Nashivochnikova1, V.N. Krupin1, V.E. Leanovich2 1Privolzhsky Research Medical University, Nizhny Novgorod, Russian Federation 2JSC "Akvion", Moscow, Russian Federation Aim: to assess the efficacy of biologically active additive Cystenium II as a component of combined antimicrobial treatment of acute cystitis or exacerbation of chronic cystitis and asymptomatic bacteriuria (ASB) in pregnant women. Patients and Methods: 65 pregnant women with urinary tract infections were enrolled. Group 1 included 22 women with acute cystitis or exacerbation of chronic cystitis and group 2 included 20 women with ASB. These women received standard antimicrobial therapy (fosfomycin trometamol 3 g) and Cystenium II (1 tablet twice daily with food for 14 days). The control group included 23 women with acute cystitis or exacerbation of chronic cystitis or ASB who received standard antimicrobial therapy only. Treatment results were evaluated after 14 days and 2 months. Results: complete resolution of cystitis occurred on days 2 and 3 in group 1 and days 4 and 5 in group 2. Eradication of causative agent as demonstrated by inoculation of urine samples after 14 days was reported in 77.3% of women in group 1, 70% of women in group 2, and 61% of women in group 3. Total treatment efficacy in group 1 was 81.9%, i.e., exacerbations of chronic cystitis were diagnosed in 3 women (13.6%), acute pyelonephritis in 1 woman (4.5%). Total treatment efficacy in group 2 was 90%, i.e., recurrence of ASB was diagnosed in 2 women (10%). Meanwhile, treatment efficacy in the control group was 56.5%, i.e., clinical exacerbation of chronic cystitis was diagnosed in 6 women (26%). Moreover, in 4 women (17.4%), the disease was complicated by acute pyelonephritis. Conclusions: Cystenium II for acute cystitis or exacerbation of chronic cystitis and ASB in pregnant women improves treatment success and also maintains the effect. Keywords: cystitis, asymptomatic bacteriuria, pregnancy, treatment, cranberry, prevention of recurrences. For citation: Nashivochnikova N.A., Krupin V.N., Leanovich V.E. Prevention and treatment of non-complicated infections  of the lower urinary tract in pregnant women. Russian Journal of Woman and Child Health. 2021;4(2):119-123. DOI: 10.32364/2618-8430-2021-4-2-119-123.